DAMPAK PANDEMI TERHADAP USAHA MIKRO PARTNER GRAB-FOOD DI KELURAHAN KETINTANG SURABAYA - Fitoni Mahmuddin (Jurnal Ekonomi dan Bisnis (EK&BI), 2020)
The policies issued by the government to prevent the spread of COVID-19 have an impact on the economy, including the micro economy. This study was made with the aim of knowing the impact of policies in handling pandemics and the factors that affect the income of micro business owners who partner with grabfood as well as to compare the income earned before and after the pandemic and to find out how the application of technology impacts traders in Ketintang Surabaya during the pandemic. This research uses descriptive qualitative method. The results showed that the policies during the pandemic had an impact on micro businesses in the form of a drastic decrease in the number of buyers, decreased income and business closures.